FUTURE MODERN RETAIL SOLUTIONS AND SHOPPER EXPERIENCE - JELEV, Viorica (Annals of Spiru Haret University. Economic Series, 2018)
Artificial intelligence and automation will radically change the world, but if we want society to benefit from these changes, we need to properly prepare ourselves through an education tailored to new times. Until the last century, it was the manufacturing industry that created jobs. But today, as a result of the existence of artificial intelligence, robots, the manufacturing industry is no longer the main driver of job creation but the service industry. As competition grows, brand manager imagination needs to work, and sales growth solutions need to focus on customer focus attention. It is a difficult task if all brands offer discounts in the malls they are in, and the announcement of differentiation is put to the attention of specialists who offer solutions for fun of any kind for the clients. The article aims to present the evolution of world trade in recent years and the various ways of diversion invented by retailers to keep customers in store chains longer time for them to buy more. The conclusion of this article will focus on the idea of future trade based on modern technology inside stores, which will lead to profound changes in customer buying behavior.